Charles Doughty, un orientaliste engagé - Catherine DELMAS (E-REA)
Charles Montagu Doughty (1843-1926) was a scientist and a poet who explored Arabia for two years, from 1876 to 1878, after a Grand Tour of Europe and the Middle East in order to complete his education and his training as a geologist and a linguist. Travels in Arabia Deserta (1888) is both a geological treatise, a topographical and cartographic survey, an archeological and epigraphic study and an anthropological narrative, in which the scientific dimension dovetails with a mimetic and axiological function. The plurality of his various fields of interest raises the issue of his involvement at the service of his nation, even though he was neither a conqueror nor a colonizer. He defended the advancement of Western knowledge, the ideological values and Christian beliefs of his country, and the purity of the English language.